Study on Chemical and Bioactive Components of Different Floral Sources’ Honey in Nepal - Bhattarai, Samiksha; Subedi, Ujjwol; Bhattarai, Uttam Kumar; Karki, Roman; Ojha, Pravin (Journal of Food Science and Technology Nepal, 2019)
Honey samples of commercial honey bee (Apis mellifera) were collected from different bee keepers in Nepal. Total 16 different samples from Dang, Chitwan, Nawalparasi, Sarlahi, Makwanpur and Rautahat districts of Nepal were obtained, representing honey of 4 different floral sources ‘Chiuri’ (Diploknema butyracea), ‘Rudhilo’ (Pogostemon plectranthoides), Mustard (Brassica napus), and Buckwheat (Fagopyrum esculentum). Chemical composition and bioactive components of the honey samples were studied.Moisture content, pH, total acidity of the examined honey samples was found to be in the range of 19.30 ± 0.87 to 20.15 ± 1.39 %, 3.35 ± 0.63 to 4.80 ± 0.15, 109.25 ± 2.06 to 191.25 ± 14.73 meq/kg, respectively. Antioxidant activity, polyphenol, and flavonoid content were found to be in the range of 51.51 ± 4.95 to 97.84 ± 3.75 %, 17.82 ± 1.61 to 59.34 ± 2.77 mg GAE/100g, 1.22 ± 0.65 to 3.86 ± 0.80 mg GAE/100g, respectively. TSS, reducing sugars and HMF content ranged from 77.5 ± 0.46 to 78.0 ± 0.91 oBx, 64.06 ± 1.99 to 70.76 ± 1.26%, and 49.5 ± 4.50 to 214 ± 39.20 mg/kg respectively.